Intestinal antiinflammatory activity of a lyophilized infusion of Turnera ulmifolia in TNBS rat colitis - Galvez, Julio; Gracioso, Juliano de Souza; Camuesco, Desiree; Vilegas, Wagner [UNESP]; Monteiro Souza Brito, Alba Regina; Zarzuelo, Antonio (Elsevier B.V., 2006)
Turnera ulmifolia is a plant popularly known in Brazil and South America as chanana. Some species of Turnera are widely used in folk medicine for different types of inflammatory diseases. In this study, the preventive intestinal antiinflammatory activity of a lyophilized infusion obtained from the aerial parts of T. ulmifolia was tested in the trinitrobenzenesulphonic acid (TNBS) model of rat colitis. The results obtained revealed that pretreatment to colitic rats with the extract, at 250 and 500 mg/kg, significantly attenuated the colonic damage induced by TNBS. This beneficial effect was associated with an improvement in the colonic oxidative status, since the infusion prevented the glutathione depletion that occurred as a consequence of the colonic inflammation. on the other hand, this antioxidant activity was confirmed in in vitro studies. In conclusion, the preventive effect exerted by the lyophilized infusion of T. ulmifolia in the TNBS model of rat colitis is probably related to its antioxidant properties, due to its flavonoids content. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Turnera ulmifolia; antiinflammatory; rat colitis